PRESENCE OF Cronobacter spp. AND SOME QUALITY CHARACTERISTICS OF THE POWDERED INFANT FORMULA - Tokatli Demirok, Nazan; Arici, Muhammet (YILDIZ TECHNICAL UNIV, 2019)
Cronobacter species are opportunistic food-borne pathogens that can cause severe and sometimes lethal infections (meningitis, bacteraemia, and necrotizing enterocolitis) predominantly in neonates and have been frequently isolated from different environments, plant materials (cereals, herbs and spices), and various foods, including powdered infant formula (PIF). Infants and newborns may infected through contaminated PIF with Cronobacter. The purpose of this study was to determine Cronobacter spp., total mesophilic aerobic bacteria count, coliform bacteria count and evaluate physicochemical properties in infant formula as well. Sixty two PIF samples were collected from different companies. In the studied formulas, Cronobacter spp. was identified in three (4.8%) of all PIF samples. The average total mesophilic aerobic bacteria and coliform bacteria numbers were found as 2.66 log cfu/g and 1.32 log cfu/g, respectively. The total sugar, invert sugar and protein content of PIF examples were found 49.12%, 32.36%, and 11.24%, respectively. In conclusion, this study results showed the prevalence of Cronobacter spp. from PIF and demonstrating a potential risk for infants in Turkey.
Keywords: Powder infant formula; physicochemical and microbiological properties; Cronobacter spp.; ENTEROBACTER-SAKAZAKII; MILK; PREVALENCE; IDENTIFICATION; PATHOGEN; PROVINCE; Engineering